A direct method for the N-tetraalkylation of azamacrocycles - Counsell, Andrew J.; Jones, Angus T.; Todd, Matthew H.; Rutledge, Peter J. (Beilstein Journal of Organic Chemistry, 2016)
An efficient protocol for the direct synthesis of N-tetraalkylated derivatives of the azamacrocycles cyclam and cyclen has been developed, using a partially miscible aqueous–organic solvent system with propargyl bromide, benzyl bromide, and related halides. The method works most effectively when the reaction mixture is shaken, not stirred. A crystal structure of the N-tetrapropargyl cyclam derivative 1,4,8,11-tetra(prop-2-yn-1-yl)-1,4,8,11-tetraazacyclotetradecane diperchlorate is reported.
Keywords: azamacrocycles; biphasic system; cyclam; cyclen; N-alkylation